Simplified Method for Stablization of Bonded Lingual Retainer - Shrestha, Raju; Halwai, Hemant Kumar; Yadav, Sumit Kumar; Dutta, Kishor (Orthodontic Journal of Nepal, 2017)
After completion of orthodontic treatment, retention is the most important step for prevention of relapse. Many direct and indirect techniques for placing a bonded lingual retainer have been practiced over the years. Present clinical practice demands a convenient technique for bonding a lingual retainer. This article describes a simplified technique of bonding a lingual retainer.